Evolution of the endothelin pathway drove neural crest cell diversification - Square, Tyler A; Jandzik, David; Massey, James L; Romášek, Marek; Stein, Haley P; Hansen, Andrew W; Purkayastha, Amrita; Cattell, Maria V; Medeiros, Daniel M (Nature, 2020)
Neural crest cells (NCCs) are migratory, multipotent embryonic cells that are unique to vertebrates and form an array of clade-defining adult features. The evolution of NCCs has been linked to various genomic events, including the evolution of new gene-regulatory networks1,2, the de novo evolution of genes3 and the proliferation of paralogous genes during genome-wide duplication events4. However, conclusive functional evidence linking new and/or duplicated genes to NCC evolution is lacking. Endothelin ligands (Edns) and endothelin receptors (Ednrs) are unique to vertebrates3,5,6, and regulate multiple aspects of NCC development in jawed vertebrates7-10. Here, to test whether the evolution of Edn signalling was a driver of NCC evolution, we used CRISPR-Cas9 mutagenesis11 to disrupt edn, ednr and dlx genes in the sea lamprey, Petromyzon marinus. Lampreys are jawless fishes that last shared a common ancestor with modern jawed vertebrates around 500 million years ago12. Thus, comparisons between lampreys and gnathostomes can identify deeply conserved and evolutionarily flexible features of vertebrate development. Using the frog Xenopus laevis to expand gnathostome phylogenetic representation and facilitate side-by-side analyses, we identify ancient and lineage-specific roles for Edn signalling. These findings suggest that Edn signalling was activated in NCCs before duplication of the vertebrate genome. Then, after one or more genome-wide duplications in the vertebrate stem, paralogous Edn pathways functionally diverged, resulting in NCC subpopulations with different Edn signalling requirements. We posit that this new developmental modularity facilitated the independent evolution of NCC derivatives in stem vertebrates. Consistent with this, differences in Edn pathway targets are associated with differences in the oropharyngeal skeleton and autonomic nervous system of lampreys and modern gnathostomes. In summary, our work provides functional genetic evidence linking the origin and duplication of new vertebrate genes with the stepwise evolution of a defining vertebrate novelty.
Keywords: Animals; Heart; receptory endotelinů; Cell Lineage; Female; Endothelins; Receptors, Endothelin; Bone Development; buněčný rodokmen; ženské pohlaví; srdce; Xenopus; kosti a kostní tkáň; signální transdukce; Evolution, Molecular; molekulární evoluce; Neural Crest; Signal Transduction; Ligands; hlava; Male; endoteliny; vývoj kostí; Petromyzon; Larva; zvířata; mužské pohlaví; Head; crista neuralis; Bone and Bones; ligandy; larva